Two Distinct Genotypes of Spissistilus festinus (Say, 1830) Reproduce and Differentially Transmit Grapevine Red Blotch Virus - Flasco, Madison T.; Fuchs, Marc F. (Insects (Basel, Switzerland), 2023)
Two phenotypically similar but genetically distinct genotypes of Spissistilus festinus (Say, 1830) (Hemiptera: Membracidae), a pest of legume crops in Southern United States and a vector of grapevine red blotch virus (GRBV) in California vineyards, exist. No information is available on whether the two S. festinus genotypes, i.e., California (CA) and Southeastern (SE), are sexually compatible or whether the SE genotype can transmit GRBV. In this study, we established mixed mating S. festinus pairs for which the F1 offspring varied phenotypically compared with the offspring of same genotype pairs but acquired GRBV isolate NY175 at similar rates (p = 0.96) and with a similar viral genome copy number (p = 0.34). Likewise, rates of GRBV acquisition were alike for the two parental CA (58%, 61/105) and SE (61%, 65/106) genotypes (p = 0.74), though the GRBV copy number in the salivary glands was overall significantly higher for SE than CA individuals (p = 0.02). Furthermore, the GRBV transmission rate was significantly higher for the SE genotype (89%, 16/18) than the CA genotype (50%, 8/16) (p = 0.04). These results revealed the existence of two sexually compatible S. festinus genotypes with distinct GRBV transmission abilities, suggesting the need to study GRBV ecology in Southeastern United States and areas where the two genotypes might co-exist.